ROLE OF PSYCHOLOGICAL CAPITALIN DEALING WITH THE BUSINESS CHALLENGES FACED BY ENTREPRENEURS - Umerlshfaq,; Ahmed Khooharo, Tanveer; Wadood, Fazli (The journal of contemporary issues in business and government, 2022)
Psychological capital (PsyCap) can be cited as “ HERO” ,comprising of four factors (Hope, Self-Efficacy, Resilience and Optimism) and has been gaining a lot of prominence in many of the social science studies particularly studies pertaining to leadership.(Juhdi, Hamid, Rizal, & Juhdi, 2015) found that there exists a relation between entrepreneurial success and psychological capital. The present study reports the results of a survey conducted among successful Indian entrepreneurs. This paper explains about the various challenges faced by entrepreneurs and their psychological capital in dealing with the challenges. A selfadministered questionnaire was distributed to 209 entrepreneurs with more than 5 years of entrepreneurial experience, working in different sectors in India. The survey explored the role of PsyCap in entrepreneurs in dealing with their early and current business challenges. The results show that successful entrepreneurs tend to have an above average level of PsyCap and Optimism and Self-Efficacy plays and more significant role as compared to Hope and Resilience for an entrepreneur to be successful. It was also found that women entrepreneurs have a higher level of PsyCap as compared to men entrepreneurs.